If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -27 = 95 Reorder the terms: -27 + 2x = 95 Solving -27 + 2x = 95 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 2x = 95 + 27 Combine like terms: -27 + 27 = 0 0 + 2x = 95 + 27 2x = 95 + 27 Combine like terms: 95 + 27 = 122 2x = 122 Divide each side by '2'. x = 61 Simplifying x = 61
| 10-6x=20-26x | | 3x^2-4x+119=0 | | 70-2x=85-3x | | 4/d=12 | | y^2-8y+154=0 | | 4x-32=3x+10 | | -0.33-m=-0.11m+0.037-0.33m | | -40=(x-10) | | 10-4x=30-44x | | -2(-2)-4(-2)= | | 323=-1+6(8a+6) | | 84-2x=98-3x | | -2x-2-4(-2)= | | 2-7(m-8)=114 | | Y=g(x-2) | | 1/9×=4 | | (X+3)4=y | | 9a^4x^5/4x/3a/2x | | 3(4-5n)=-78 | | 0.25k=3(-0.75k+3) | | 2v=v+13 | | 2b=b+88 | | 0.1(x-3)=1.1-0.25 | | b+10+7b=10 | | Z(2z+6)=3+z | | 4t-54=3t-9 | | 2n+6=48-5n | | -7n+10n=-33 | | (2(x^(1/2)))^2 | | 5t-92=t | | 1+7x+3x=21 | | 4p-32=p+31 |